The relationship between human resource management practices and employee retention in federation of Malaysian manufacturers - Norlidaemi, Nordin (2023)
This study is conducted to examine the relationship between employee retention and human resource practices which are employee empowerment, performance appraisal and compensation. Employee retention is a critical concern for organisations seeking to maintain a competitive edge in today’s dynamic business environment. For employers, knowing how to retain employees is wiser than to prevent them from quitting jobs. The main idea of this research is to explore and investigate on the human resource practices that affect employee retention such as employee empowerment, performance appraisal and compensation in Federation of Malaysian Manufacturer (FMM). These three human resources practices were chosen based on the main issues selected during the exit interview conducted. This quantitative study uses a questionnaire to collect data from employees based on simple random sampling. A total of 123 questionnaire were distributed in hardcopies form to all FMM employees. At the end of data collection period a total of 100 questionnaire been return. The results shows that all the three variables (employee empowerment, performance appraisal and compensation) are significant and has a positive influence on employee retention. The findings from this study are adequate to be used as references by companies and this also can help the management especially human department to aware and take all the necessary steps to retain employees.